2014
DOI: 10.1007/s12010-014-1319-y
|View full text |Cite
|
Sign up to set email alerts
|

Surface Plasmon Resonance Based Label-Free Detection of Salmonella using DNA Self Assembly

Abstract: Typhoid is re-emerging as a biggest health threat to third world countries. One of the major challenge is false negative diagnosis using existing immunodiagnostic methods due to overlapping symptoms of other infections (like brucellosis, malaria, hepatitis) that mimic this enteric fever (typhoid). Surface plasmon resonance (SPR) based DNA hybridisation biosensor has been fabricated by generating self-assembled monolayer of 5'-thiolated single-stranded DNA (ssDNA) probe onto gold surface. Highly specific DNA pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 37 publications
0
12
0
1
Order By: Relevance
“…From the recovered bacteria species, 128 were identified as Salmonella Typhi, the isolates stereotyping showed that; 9 groups (75%) had the antigenic formula O:9(D 1 ) for Salmonella Typhi, 3 groups (25%) had the formula Salmonella enteric Paratyphi A 1,2,12 a [ 1 , 5 ] and Salmonella enterica Paratyphi C1 6,7,[Vi] c 1,5 respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the recovered bacteria species, 128 were identified as Salmonella Typhi, the isolates stereotyping showed that; 9 groups (75%) had the antigenic formula O:9(D 1 ) for Salmonella Typhi, 3 groups (25%) had the formula Salmonella enteric Paratyphi A 1,2,12 a [ 1 , 5 ] and Salmonella enterica Paratyphi C1 6,7,[Vi] c 1,5 respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Globally the burden of typhoid fever victims are 20 million as a main issue of morbidity and mortality in developing countries [ 1 , 2 ]. In Sudan, approximate numbers of typhoid infection is increasing during rainy season in association with malaria incidents [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…An SPR-based genoassay has been performed to detect S. Typhi based on thiolated self-assembled monolayer of single-stranded DNA (ssDNA) as a DNA probe, which is designed for the Vi-antigen gene of S. Typhi [ 130 ]. In this study, specific ssDNA probes were immobilized onto gold film, and the assay records the lowest detection concentration (0.019 ng/mL −1 ), when compared to several other SPR-based bacterial detection studies ( Table 3 ).…”
Section: Laboratory Diagnostic Approachesmentioning
confidence: 99%
“…Another group has assembled a SPR based DNA hybridization biosensor immobilized with ssDNA probe complementary to conserved Vi capsular protein of Salmonella enteric Serovars typhi. The biosensor works at room temperature up to 40 hybridization cycles and differentiate between complementary and mismatched sequences [38].…”
Section: Salmonella Typhimentioning
confidence: 99%